Provision of immunoglobulins to suckling piglets can enhance post-weaning growth performance : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Animal Science at Massey University - Vanavichial, Boonkasem (Massey University, 1998)
In this experiment the hypothesis that providing a supplementary source of bovine milk immunoglobulin G (IgG) to suckling piglets increases post-weaning growth performance was tested. The litters from eight multiparous Large White x Landrace sows received oral supplements by syringe. Three piglets in each litter received oral doses of whey globulin concentrate (WGC) which contained 6% IgG. A second group of three piglets per litter received oral doses of whey protein isolate (WPI) to approximate the amino acids supplied in WGC but without IgG's. A third group of three piglets per litter received oral doses of water (CONT) to simulate the oral dosing procedure. The daily supplement of WGC and WPI provided 0.7 g per day of age of ideal protein during the first week and 1.4 g per day of age thereafter. The oral doses were provided twice daily at 09.00h and 15.00h from day 2 to day 24 of lactation. For the statistical analysis, a linear model including sex, sow and treatment as fixed effects, and live weight at birth as covariate was fitted to the data. The average daily gains measured over the suckling period (24d) were not atatistically significantly different between the three groups with the control gaining 249gd-1, WGC gaining 259gd-1 and WPI gaining 264gd-1. The provision of either WGC or WPI did not increase the average daily gain up to weaning, possibly because the piglets reduced their intake of sow's milk. To determine the effect of supplemental IgG, the most valid comparison is between WPI and WGC because the supply of ideal protein, and the time taken to provide each oral dose, were similar. Piglets receiving WGC grew 12% faster than WPI from transfer (62d) to slaughter (85kg) (P < 0.05), and 8% faster from birth to slaughter (P < 0.05). These findings indicate that the provision of IgG during early life can lead to long term advantages in growth rate.
Keywords: Pig growth; Pig feed; Immunoglobulins